Y / Beta composite double-microporous material and preparation method thereof
By using nano-scale Beta molecular sieve precursor and small grain NaY molecular sieve, the preparation of Y/Beta composite double microporous materials is achieved, and the problem of low specific surface area and pore volume of composite molecular sieve products in the prior art is solved, and the catalytic activity is improved.
Patent Information
- Application Number
- CN202311435910.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-10-31
AI Technical Summary
The existing synthesis method of Y/Beta composite molecular sieve is difficult to ensure the recombination of Y-type molecular sieve and Beta-type molecular sieve at the microscopic level, resulting in a low specific surface area and pore volume of the obtained composite molecular sieve product, affecting catalytic activity.
The nanoscale Beta molecular sieve precursor and small crystal NaY molecular sieve are used as combined moieties to achieve the preparation of Y/Beta composite double microporous materials through specific mixing and crystallization steps.
The composite between Y and Beta molecular sieve particles at the nano-level is achieved, which improves the specific surface area and pore volume of the Y/Beta composite double-porous material and improves the catalytic activity.
Smart Images

Figure CN119911927A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a Y / Beta composite double microporous material and a preparation method thereof. Background Art
[0002] Among the hundreds of molecular sieves that have been developed, the Y-type molecular sieve is the most widely used in industry. At present, the synthesis of NaY molecular sieves in industry mainly adopts the seed gel method. Due to the use and improvement of seed gel, the crystallization time of Y-type molecular sieves has been greatly shortened, laying the foundation for the industrialization of Y-type molecular sieves. Beta zeolite is the only large-pore high-silica zeolite with a three-dimensional cross-twelve-membered ring channel structure discovered so far. It shows excellent catalytic performance in hydrocarbon hydrocracking, hydroisomerization, alkane aromatization, alkylation and transalkylation reactions.
[0003] Y and Beta molecular sieves have different characteristics due to their different crystal structures, micropore texture properties and elemental compositions: Y molecular sieves have supercage structures and three-dimensional pore systems, and have good adsorption properties, rich micropores and uniform pore sizes; Beta molecular sieves have good hydrothermal stability, and exhibit good resistance to carbon deposition and long service life in catalysis. In addition, Y molecular sieves and Beta molecular sieves have different basic structural units and belong to molecular sieve systems with different topological structures. During the synthesis process, there are significant differences in the composition of the crystallization liquid and the crystallization conditions of the two, and it is impossible to synthesize them in one step through the "eutectic method". The existing synthesis methods of Y / Beta composite molecular sieves usually cannot ensure the composite of Y molecular sieves and Beta molecular sieves at the microscopic level, and the specific surface area and pore volume of the resulting composite molecular sieve products are low, which affects the catalytic activity. Summary of the invention
[0004] The purpose of the present disclosure is to provide a Y / Beta composite dual microporous material and a preparation method thereof, so as to increase the specific surface area and pore volume of the Y / Beta composite dual microporous material.
[0005] In order to achieve the above object, the present disclosure provides a first aspect of a method for preparing a Y / Beta composite dual microporous material, the method comprising the following steps:
[0006] Obtaining Beta molecular sieve precursor and small-grain NaY molecular sieve respectively;
[0007] The Beta molecular sieve precursor, the small-grain NaY molecular sieve, an optional dual-microporous material synthesis template, an optional dual-microporous material synthesis alkali source and optional water are mixed to obtain a synthetic mixture;
[0008] The synthesis mixture is subjected to dual microporous material synthesis crystallization.
[0009] Optionally, the preparation steps of the Beta molecular sieve precursor include:
[0010] Mixing a first aluminum source, a first silicon source, a first template and a first alkali source to obtain a first mixture;
[0011] Performing a first crystallization on the first mixture to obtain the Beta molecular sieve precursor;
[0012] Wherein, calculated in terms of oxides and in terms of moles, the composition of the first mixture is M:A12O3:SiO2:R:H2O=(2-9):1:(15-40):(2-5):(100-400), where M represents an alkali metal oxide and R represents the first template.
[0013] Optionally, the first aluminum source is one or more selected from aluminum sulfate, aluminum chloride, aluminum nitrate, sodium metaaluminate and pseudo-boehmite;
[0014] The first silicon source is one or more selected from water glass, colloidal silicon dioxide, silica sol and white carbon black;
[0015] The first template is one or more selected from tetraethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide;
[0016] The first alkali source is one or more selected from sodium hydroxide, potassium hydroxide, sodium oxide and potassium oxide.
[0017] Optionally, the first crystallization conditions include: a temperature of 110 to 155° C. and a time of 12 to 72 hours.
[0018] Optionally, the particle size of the small-grain NaY molecular sieve is 100-500 nm.
[0019] The preparation steps of the small-grain NaY molecular sieve include:
[0020] Mixing sodium aluminate and water glass at a temperature of 15 to 60° C. and under stirring conditions to obtain a second mixture, wherein the composition of the second mixture is Na2O:A12O3:SiO2=(6 to 25):1:(6 to 25) in terms of oxides and moles;
[0021] Stirring the second mixture at 15 to 60° C. for 5 to 48 hours, and then statically aging at 15 to 60° C. for 5 to 48 hours to obtain a third mixture;
[0022] Adding water to the third mixture under stirring conditions to obtain a directing agent, wherein the directing agent has a composition of Na2O:A12O3:SiO2:H2O=(6-25):1:(6-25):(200-400) in terms of oxides and moles;
[0023] Mixing the second silicon source and the second aluminum source with the directing agent to obtain a fourth mixture, wherein the composition of the fourth mixture is Na2O:A12O3:SiO2:H2O=(6-25):1:(6-25):(200-400) in terms of oxides and moles, and the molar number of the aluminum element in the directing agent accounts for 3-30% of the molar number of the total aluminum element in the fourth mixture;
[0024] The fourth mixture is subjected to a third crystallization at 90-100° C. for 15-48 hours, and the small-grain NaY molecular sieve is obtained after washing and filtering.
[0025] Optionally, the second silicon source is one or more selected from water glass, silica sol, silica gel and white carbon black;
[0026] The second aluminum source is one or more selected from the group consisting of sodium aluminate, aluminum sulfate, aluminum chloride, aluminum nitrate, aluminum hydroxide and pseudo-boehmite.
[0027] Optionally, the weight ratio of the Beta molecular sieve precursor, the small-grain NaY molecular sieve, the dual-microporous material synthesis template, the dual-microporous material synthesis alkali source and the water is 1: (0.1-10): (0-0.4): (0-1): (0-10).
[0028] Optionally, the template for synthesizing the dual microporous material is one or more selected from tetraethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide;
[0029] The double microporous material synthetic alkali source is one or more selected from sodium hydroxide, potassium hydroxide, sodium oxide and potassium oxide.
[0030] Optionally, the conditions for synthesizing and crystallizing the dual microporous material include: a temperature of 110 to 155° C. and a time of 12 to 60 hours.
[0031] In a second aspect of the present disclosure, a Y / Beta composite dual microporous material is provided which is prepared by the method described in the first aspect of the present disclosure.
[0032] Through the above technical scheme, the present invention adopts nano-scale Beta molecular sieve precursor and small-grain NaY as combined elements to synthesize Y / Beta composite dual-microporous material, realizing the composite between two different crystalline molecular sieve particles at the nano level. The obtained Y / Beta composite dual-microporous material has a higher specific surface area and pore volume.
[0033] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0035] Figure 1 This is the XRD spectrum of the Y / Beta composite double microporous material prepared in Example 1.
[0036] Figure 2 This is the SEM image of the Y / Beta composite double microporous material prepared in Example 1.
[0037] Figure 3 This is the SEM image of the Y / Beta composite double microporous material prepared in Comparative Example 1. DETAILED DESCRIPTION
[0038] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0039] In a first aspect, the present disclosure provides a method for preparing a Y / Beta composite dual microporous material, the method comprising the following steps:
[0040] Obtaining Beta molecular sieve precursor and small-grain NaY molecular sieve respectively;
[0041] The Beta molecular sieve precursor, the small-grain NaY molecular sieve, an optional template for synthesis of dual microporous materials, an optional alkali source for synthesis of dual microporous materials and water are mixed to obtain a synthetic mixture;
[0042] The synthesis mixture is subjected to dual microporous material synthesis crystallization.
[0043] According to the present disclosure, the Beta molecular sieve precursor has a nanometer size. Specifically, the particle size of the Beta molecular sieve precursor may be 50 to 100 nm.
[0044] In one embodiment, the preparation step of the Beta molecular sieve precursor may include:
[0045] Mixing a first aluminum source, a first silicon source, a first template and a first alkali source to obtain a first mixture;
[0046] Performing a first crystallization on the first mixture to obtain the Beta molecular sieve precursor;
[0047] Wherein, calculated in terms of oxides and in terms of moles, the composition of the first mixture is M:A12O3:SiO2:R:H2O=(2-9):1:(15-40):(2-5):(100-400), where M represents an alkali metal oxide and R represents the first template.
[0048] Among them, the first aluminum source, the first silicon source, the first template, and the first alkali source can be common types of synthetic Beta molecular sieves, respectively; specifically, the first aluminum source can be one or more selected from aluminum sulfate, aluminum chloride, aluminum nitrate, sodium aluminate and pseudo-boehmite, preferably one or more of aluminum sulfate, sodium aluminate and pseudo-boehmite; the first silicon source can be one or more selected from water glass, colloidal silica, silica sol and white carbon black, preferably colloidal silica and / or white carbon black; the first template can be one or more selected from tetraethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide, preferably tetraethylammonium hydroxide and / or tetrapropylammonium hydroxide; the first alkali source can be one or more selected from sodium hydroxide, potassium hydroxide, sodium oxide and potassium oxide, preferably sodium hydroxide and / or potassium hydroxide.
[0049] The first crystallization may be performed under a closed condition. Specifically, the conditions for the first crystallization may include: a temperature of 110 to 155° C. and a time of 12 to 72 hours.
[0050] According to the present disclosure, the particle size of the small-grain NaY molecular sieve may be 100 to 500 nm.
[0051] The small-grain NaY molecular sieve can be synthesized by a method well known to those skilled in the art. In one embodiment, the preparation steps of the small-grain NaY molecular sieve include:
[0052] Mixing sodium aluminate and water glass at a temperature of 15 to 60° C. and under stirring conditions to obtain a second mixture, wherein the composition of the second mixture is Na2O:A12O3:SiO2=(6 to 25):1:(6 to 25) in terms of oxides and moles;
[0053] Stirring the second mixture at 15 to 60° C. for 5 to 48 hours, and then statically aging at 15 to 60° C. for 5 to 48 hours to obtain a third mixture;
[0054] Adding water to the third mixture under stirring conditions to obtain a directing agent, wherein the directing agent has a composition of Na2O:A12O3:SiO2:H2O=(6-25):1:(6-25):(200-400) in terms of oxides and moles;
[0055] Mixing the second silicon source and the second aluminum source with the directing agent to obtain a fourth mixture, wherein the composition of the fourth mixture is Na2O:A12O3:SiO2:H2O=(6-25):1:(6-25):(200-400) in terms of oxides and moles, and the molar number of the aluminum element in the directing agent accounts for 3-30% of the molar number of the total aluminum element in the fourth mixture;
[0056] The fourth mixture is subjected to a second crystallization at 90-100° C. for 15-48 hours, and the small-grain NaY molecular sieve is obtained after washing and filtering.
[0057] The second silicon source and the second aluminum source may be common species for synthesizing NaY molecular sieves; specifically, the second silicon source may be one or more selected from water glass, silica sol, silica gel and white carbon black; the second aluminum source may be one or more selected from sodium aluminate, aluminum sulfate, aluminum chloride, aluminum nitrate, aluminum hydroxide and pseudo-boehmite. The water may be deionized water or distilled water.
[0058] According to the present disclosure, in the synthesis mixture, the weight ratio of the Beta molecular sieve precursor, the small-grain NaY molecular sieve, the dual-microporous material synthesis template, the dual-microporous material synthesis alkali source and the water can be 1: (0.1-10): (0-0.4): (0-1): (0-10), preferably, the weight ratio of the Beta molecular sieve precursor, the small-grain NaY molecular sieve, the dual-microporous material synthesis template, the dual-microporous material synthesis alkali source and the water is 1: (1-9): (0.04-0.4): (0.0001-1): (0.09-10). The dual-microporous material synthesis template can be one or more selected from tetraethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide; the dual-microporous material synthesis template and the first template can be the same template or different templates, preferably the same template. The dual microporous material synthetic alkali source is one or more selected from sodium hydroxide, potassium hydroxide, sodium oxide and potassium oxide; the dual microporous material synthetic alkali source and the first alkali source can be the same alkali source or different alkali sources, preferably the same alkali source.
[0059] The Beta molecular sieve precursor, the small-grain NaY molecular sieve, the template for synthesis of dual microporous materials, the alkali source for synthesis of dual microporous materials and water are preferably mixed under stirring conditions.
[0060] According to the present disclosure, the conditions for the synthesis and crystallization of the dual microporous material may include: a temperature of 110 to 155° C. and a time of 12 to 60 hours.
[0061] According to the present disclosure, the method further comprises the steps of filtering, washing, drying and calcining the crystallized product obtained by the synthesis and crystallization of the dual microporous material, wherein the drying and calcining conditions may be conventional in the art.
[0062] The Y / Beta composite dual microporous material disclosed herein uses a nanoscale Beta molecular sieve precursor and a small-grain NaY molecular sieve as a combination unit, achieving a composite between molecular sieve particles of different crystal forms at the nano level, while also ensuring relatively high grain integrity and relative crystallinity of the two molecular sieves.
[0063] In a second aspect of the present disclosure, a Y / Beta composite dual microporous material prepared by the method described in the first aspect of the present disclosure is provided. The weight percentage of the Y molecular sieve can be adjusted between 5 and 95% as needed. The present disclosure realizes the composite between two different crystalline molecular sieve particles at the nanometer level. The Y / Beta composite dual microporous material has a high specific surface area and pore volume. Specifically, the specific surface area of the Y / Beta composite dual microporous material can be 720 to 750 m 2 / g, the pore volume can be 0.34~0.39cm 3 / g.
[0064] The present disclosure is further described below in conjunction with examples and comparative examples, but the scope of the present disclosure is not limited to these examples.
[0065] In each embodiment and comparative example, the specific surface area and pore structure were measured using the ASAP2420 automatic adsorption instrument and ASAP2020 automatic adsorption instrument of the American Micromeritics Instrument Company, and the total pore volume and secondary pore volume of the molecular sieve were calculated according to the BET method. The specific steps are as follows: the BET specific surface is specified in the nitrogen partial pressure range of 0.05 to 0.35 MPa, 3 to 5 pressures are selected, the actual nitrogen adsorption amount is measured, and then the specific surface area is calculated using the BET equation. The micropore volume and total pore volume are calculated according to the t-plot curve, and the secondary pore volume is calculated by the BJH formula.
[0066] Example 1
[0067] (1) Preparation of Beta molecular sieve precursor
[0068] 18.4g TEAOH (Aladdin, analytical grade, 25% aqueous solution, the same below), 5.4g sodium aluminate (provided by Sinopec Catalyst Changling Branch, Al2O3 content is 101.5g / L, Na2O content is 142.5g / L, specific gravity is 1.17, the same below), 0.50g NaOH (Shanghai test, analytical grade, ≥96%, the same below), 0.70g aluminum sulfate (Sinopharm Chemical Reagent Co., Ltd., analytical grade) were added. , the same below) and 10g of white carbon black (Shanghai test, analytical grade, ≥99%, the same below) are mixed and stirred into a uniform white colloid, loaded into a 100mL stainless steel reactor, crystallized at 110°C for 72h, and taken out for use. The original material molar ratio of the Beta molecular sieve precursor is: 2.5Na2O:A12O3:25.2SiO2:4.7(TEA)2O:149.5H2O, and the particle size of the Beta molecular sieve precursor is 100nm.
[0069] (2) Preparation of small-grain NaY molecular sieve
[0070] 50.39g of high-alkali sodium aluminate solution (provided by Sinopec Catalyst Changling Branch, Al2O3 content of 40.2g / L, Na2O content of 255g / L, specific gravity of 1.324, the same below) was added to 65.56g of water glass (provided by Sinopec Catalyst Changling Branch, SiO2 content of 260.6g / L, Na2O content of 81.6g / L, specific gravity of 1.2655, modulus of 3.3, the same below), stirred and aged at room temperature for 48 hours, then statically aged at 60°C for 5 hours, and finally 15g of deionized water was added under stirring, and the final molar ratio of the obtained directing agent was 15Na2O:A12O3:15SiO2:320H2O. The obtained directing agent was all used for the preparation of the following reaction mixture, and the amount of the directing agent added was calculated according to the molar number of aluminum element in the directing agent accounting for 3% of the total molar number of aluminum element.
[0071] Under the conditions of room temperature and high-speed stirring, the directing agent (prepared in the above steps), 1682.6g water glass, 134.19g low-alkali sodium aluminate solution (provided by the Changling Branch of Sinopec Catalyst Co., Ltd., with an Al2O3 content of 194g / L, a Na2O content of 286.2g / L, and a specific gravity of 1.413, the same below), 448.02g aluminum sulfate (provided by the Changling Branch of Sinopec Catalyst Co., Ltd., with an Al2O3 content of 88.9g / L and a specific gravity of 1.2829, the same below) and 150.4g water are added to the mixing tank in the order of 7Na2O:A12O3:12SiO2:209H2O. After being stirred evenly, it is loaded into a stainless steel reactor, statically crystallized at 100°C for 24 hours, and then filtered, washed and dried to obtain a small-grain NaY molecular sieve product, the particle size of which is 500nm.
[0072] (3) Preparation of Y / Beta composite dual microporous materials
[0073] 18.4 g TEAOH, 0.42 g NaOH, 4.5 g deionized water, 50 g Beta molecular sieve precursor prepared in step (1) and 50 g small-grain NaY molecular sieve prepared in step (2) were mixed and stirred into a uniform white colloid, placed in a 100 mL stainless steel reactor, crystallized at 120° C. for 48 h, then filtered, washed, dried at 110° C. for 6 h and calcined at 560° C. for 4 h to obtain a Y / Beta composite dual microporous material. The XRD spectrum is shown in FIG. Figure 1 ,Depend on Figure 1 It can be seen that the spectral characteristics of Y molecular sieve and Beta molecular sieve are common, wherein the Y / Beta feed weight ratio is 1:1. The SEM image of the Y / Beta composite double microporous material is as follows: Figure 2 The specific surface area and pore volume are listed in Table 1.
[0074] Example 2
[0075] The Y / Beta composite dual microporous material was prepared according to the method of Example 1, and the sources of the raw materials were the same as those of Example 1. The difference was that in step (1), the crystallization condition was 145°C for 58 hours; in step (3), the feeding amount of each material was: 2.1g TEAOH, 0.05g NaOH, 5.0g deionized water, 49.95g Beta molecular sieve precursor prepared in step (1), and 5.55g small-grained NaY molecular sieve prepared in step (2). The Y / Beta composite dual microporous material was prepared, and the XRD spectrum was the same as that of Figure 1 Similarly, the Beta / Y feed weight ratio is 9:1, and the specific surface area and pore volume of the Y / Beta composite dual microporous material are listed in Table 1.
[0076] Example 3
[0077] The Y / Beta composite dual microporous material was prepared according to the method of Example 1, and the sources of the raw materials were the same as those of Example 1. The difference was that in step (1), the crystallization condition was crystallization at 125°C for 20 hours; in step (3), the feed amounts of the materials were: 18.4 g TEAOH, 37.8 g NaOH, 405 g deionized water, 50 g Beta molecular sieve precursor prepared in step (1), and 450 g small-grain NaY molecular sieve prepared in step (2). The Y / Beta composite dual microporous material was prepared, and the XRD spectrum was the same as that of Figure 1 Similarly, the Beta / Y feed weight ratio is 1:9, and the specific surface area and pore volume of the Y / Beta composite dual microporous material are listed in Table 1.
[0078] Example 4
[0079] The Y / Beta composite dual microporous material was prepared according to the method of Example 1, and the sources of the raw materials were the same as those of Example 1. The difference was that in step (1), 10.6 g TEAOH, 8.25 g sodium aluminate and 40 g water glass were mixed and stirred into a uniform white colloid, which was then put into a 100 mL stainless steel reactor, crystallized at 140° C. for 40 h, and taken out for use. The original material molar ratio of the Beta molecular sieve precursor was: 8.3 Na2O: A12O3: 19.5 SiO2: 2.6 (TEA)2O: 346.2 H2O. In step (3), 49.93 g of the Beta molecular sieve precursor prepared in step (1) and 21.4 g of the small-grain NaY molecular sieve prepared in step (2) are mixed and stirred into a uniform white colloid, loaded into a 100 mL stainless steel reactor, crystallized at 130° C. for 36 h, and then filtered, washed, and dried to obtain a Y / Beta composite dual-microporous material, wherein the Beta / Y feed weight ratio is 7:3. The specific surface area and pore volume of the Y / Beta composite dual-microporous material are listed in Table 1.
[0080] Example 5
[0081] The Y / Beta composite dual microporous material was prepared according to the method of Example 1, and the sources of the raw materials were the same as those of Example 1. The difference was that in step (1), 10.6 g TEAOH, 8.25 g sodium aluminate and 40 g silica sol (SiO2 mass fraction 40%, Na2O mass fraction 0.5%) were mixed and stirred into a uniform white colloid, loaded into a 100 mL stainless steel reactor, crystallized at 140° C. for 40 h, and taken out for use. The original material molar ratio of the Beta molecular sieve precursor was: 2.8 Na2O: A12O3: 38.5 SiO2: 2.6 (TEA)2O: 242.2 H2O. In step (3), 18.4 g TEAOH, 37.8 g NaOH, 405 g deionized water, 192.86 g Beta molecular sieve precursor prepared in step (1) and 450 g small-grain NaY molecular sieve prepared in step (2) are mixed and stirred into a uniform white colloid, which is then placed in a 100 mL stainless steel reactor and crystallized at 120 ° C for 48 h, then filtered, washed, dried at 110 ° C for 6 hours and calcined at 540 ° C for 4 hours to obtain a Y / Beta composite dual microporous material. The XRD spectrum is consistent with that of the Figure 1 Similarly, the Beta / Y feed weight ratio is 3:7, and the specific surface area and pore volume of the Y / Beta composite dual microporous material are listed in Table 1.
[0082] Comparative Example 1
[0083] First, 70 ml of distilled water, 2 ml of concentrated sulfuric acid, 25 ml of sodium silicate solution ([SiO2] = 4.85 mol / L, [OH] = 2.75 mol / L), 11.5 ml of sodium aluminate solution ([Al2O3] = 2.09 mol / L, [OH] = 8.25 mol / L), and 3 ml of directing agent (its composition molar ratio is: 16Na2O: 15SiO2: Al2O3: 320H2O) were added in sequence and mixed into a colloid, then loaded into a 100 ml stainless steel reactor for 9 After crystallization at 0℃ for 27h, the Y-type zeolite was initially obtained for standby use; then 35ml of distilled water, 15g of TEABr (tetraethylammonium bromide), 5ml of NH3.H2O (concentrated ammonia water), the Y-type zeolite synthesized first was filtered out of the supernatant, and 45ml of silica sol ([SiO2] = 6.05mol / L) were added in sequence and mixed and stirred into a uniform white substance, and then divided into three 50ml stainless steel reactors, crystallized at 140℃ for 5 days, taken out, washed until the solution was neutral, and then dried, and then the sample was roasted at 550℃ for 5h. The SEM image of the Y / Beta composite double microporous material is shown in the figure below. Figure 3 The specific surface area and pore volume are listed in Table 1.
[0084] Comparative Example 2
[0085] 26.4g TEABr (tetraethylammonium bromide), 9ml concentrated ammonia, 5.6ml sodium aluminate solution ([Al2O3] = 2.45mol / L, [OH] = 10.37mol / L), 45ml silica sol ([SiO2] = 6.05mol / L), 50ml distilled water were mixed and stirred into a uniform white colloid, which was placed in a 100ml stainless steel reactor and crystallized at 140°C for 7 days. The product was taken out, washed until the solution was neutral, and then dried. The obtained sample was roasted at 550°C for 5h to remove the organic amine. 3.2g of calcined sample, 8ml of sodium aluminate solution ([Al2O3] = 0.25mol / L, [OH] = 1.04mol / L), 1.2g of sodium hydroxide, 37ml of distilled water, and 1.5ml of directing agent (its composition molar ratio is: 16Na2O: 15SiO2: Al2O3: 320H2O) were mixed and stirred into a uniform white substance, then loaded into a 50ml stainless steel reactor, crystallized at 90°C for 24h, taken out, washed until the solution was neutral, and then dried. The specific surface area and pore volume of the Y / Beta composite double microporous material are listed in Table 1.
[0086] Comparative Example 3
[0087] In a beaker, 11.3g sodium hydroxide, 65mL distilled water, 5.8mL sodium aluminate solution (2.88mol / L), 33mL water glass (SiO2 content 34wt%) were added successively, and the mixture was shaken vigorously, and aged at 30°C for 24h to obtain a Y structure directing agent. In a beaker, 0.8g sodium hydroxide, 1.5mL sodium aluminate (2.88mol / L), 24g white carbon black, and 100mL tetraethylammonium hydroxide (25wt%) were added successively, stirred for 3h, loaded into a synthetic bomb, and crystallized at 140°C in an oven for 5h to obtain β seed crystals. In a beaker, 100mL distilled water, 4.6g sodium hydroxide, 1.1mL sodium aluminate (2.88mol / L), 12g white carbon black, and 6mL β seed crystals were added successively, stirred for 30min, loaded into a synthetic bomb, and crystallized at 140°C in an oven for 2d to obtain a β molecular sieve slurry. Take 100mL of the β molecular sieve slurry prepared in the previous step (the dry weight of the β molecular sieve is about 4.6g), add 300mL of distilled water, 3mL of sodium aluminate (2.88mol / L), 1g of sodium hydroxide, stir for 10min, and finally add 6.5mL of Y structure directing agent, stir for 30min, then put into the synthetic bomb, and crystallize in an oven at 80℃ for 35h. The obtained product is washed with distilled water 4 times until neutral, and dried at 100℃ for 2h. The weight content of Beta molecular sieve in the composite molecular sieve is 55%. The specific surface area and pore volume of the Y / Beta composite double microporous material are listed in Table 1.
[0088] Comparative Example 4
[0089] Take 4.9ml of deionized water and place it in a 25ml beaker. Weigh 0.226g of sodium aluminate and slowly add it to the above beaker under magnetic stirring to dissolve it. Weigh 0.84g of sodium hydroxide and add it to the beaker, stir to dissolve it, wait for it to cool, then slowly add 1.7ml of silica sol, stir vigorously until uniform, continue stirring for 5min, seal and store for 18h to obtain seed glue. Take 3.2ml of deionized water and place it in a 25ml beaker. Weigh 0.226g of sodium aluminate and slowly add it to the above beaker under magnetic stirring to dissolve it. Weigh 0.25g of sodium hydroxide and add it to the beaker, stir to dissolve it, wait for it to cool, then slowly add 0.9ml of silica sol and stir vigorously for 30min. Measure 1.0ml of the seed glue prepared in the previous step and stir vigorously for 25min. Then the solution was transferred into a polytetrafluoroethylene-lined autoclave, sealed, and placed in a 90°C oven for crystallization for 2 hours to obtain a colloid containing a Y-type zeolite structural unit. Take 5.0 ml of deionized water and place it in a 100 ml beaker. Weigh 0.50 g of sodium hydroxide and add it to the beaker under magnetic stirring to dissolve it. After cooling, slowly add 14.70 ml of tetraethylammonium hydroxide solution, a colloid containing a Y-type zeolite structural unit and 9.1 ml of silica sol, continue stirring for 30 minutes, then transfer the solution into a polytetrafluoroethylene-lined autoclave, seal it, and place it in a 120°C oven for crystallization for 12 days. After the crystallization is completed, cool to room temperature, filter, wash with deionized water to pH = 7, dry at 100°C for 2 hours, calcine at 350°C in an air atmosphere for 6 hours, and cool to room temperature. The specific surface area and pore volume of the Y / Beta composite double microporous material are listed in Table 1.
[0090] Table 1
[0091] <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Example 1 745.18 0.3849 Example 2 733.45 0.3514 Example 3 733.74 0.3674 Example 4 720.93 0.3472 Example 5 749.48 0.3760 Comparative Example 1 626.49 0.3277 Comparative Example 2 613.52 0.3242 Comparative Example 3 605.83 0.3387 Comparative Example 4 627.62 0.3197
[0092] As can be seen from Table 1, the Y / Beta composite dual microporous material prepared by the method disclosed in the present invention has a higher specific surface area and pore volume.
[0093] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0094] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0095] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing a Y / Beta composite double microporous material, characterized in that: The method comprises the following steps: Obtaining Beta molecular sieve precursor and small-grain NaY molecular sieve respectively; The Beta molecular sieve precursor, the small-grain NaY molecular sieve, an optional dual-microporous material synthesis template, an optional dual-microporous material synthesis alkali source and optional water are mixed to obtain a synthetic mixture; The synthesis mixture is subjected to dual microporous material synthesis crystallization.
2. The method according to claim 1, wherein: The preparation steps of the Beta molecular sieve precursor include: Mixing a first aluminum source, a first silicon source, a first template and a first alkali source to obtain a first mixture; Performing a first crystallization on the first mixture to obtain the Beta molecular sieve precursor; Wherein, calculated in terms of oxides and in terms of moles, the composition of the first mixture is M:A12O3:SiO2:R:H2O=(2-9):1:(15-40):(2-5):(100-400), where M represents an alkali metal oxide and R represents the first template.
3. The method according to claim 2, wherein: The first aluminum source is one or more selected from aluminum sulfate, aluminum chloride, aluminum nitrate, sodium metaaluminate and pseudo-boehmite; The first silicon source is one or more selected from water glass, colloidal silicon dioxide, silica sol and white carbon black; The first template is one or more selected from tetraethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide; The first alkali source is one or more selected from sodium hydroxide, potassium hydroxide, sodium oxide and potassium oxide.
4. The method according to claim 2, wherein: The first crystallization conditions include: a temperature of 110 to 155° C. and a time of 12 to 72 hours.
5. The method according to claim 1, wherein: The particle size of the small-grain NaY molecular sieve is 100-500 nm.
6. The method according to claim 1 or 5, wherein: The preparation steps of the small-grain NaY molecular sieve include: Mixing sodium aluminate and water glass at a temperature of 15 to 60° C. and under stirring conditions to obtain a second mixture, wherein the composition of the second mixture is Na2O:A12O3:SiO2=(6 to 25):1:(6 to 25) in terms of oxides and moles; Stirring the second mixture at 15 to 60° C. for 5 to 48 hours, and then statically aging at 15 to 60° C. for 5 to 48 hours to obtain a third mixture; Adding water to the third mixture under stirring conditions to obtain a directing agent, wherein the directing agent has a composition of Na2O:A12O3:SiO2:H2O=(6-25):1:(6-25):(200-400) in terms of oxides and moles; Mixing the second silicon source and the second aluminum source with the directing agent to obtain a fourth mixture, wherein the composition of the fourth mixture is Na2O:A12O3:SiO2:H2O=(6-25):1:(6-25):(200-400) in terms of oxides and moles, and the molar number of the aluminum element in the directing agent accounts for 3-30% of the molar number of the total aluminum element in the fourth mixture; The fourth mixture is subjected to a second crystallization at 90-100° C. for 15-48 hours, and the small-grain NaY molecular sieve is obtained after washing and filtering.
7. The method according to claim 6, wherein: The second silicon source is one or more selected from water glass, silica sol, silica gel and white carbon black; The second aluminum source is one or more selected from the group consisting of sodium aluminate, aluminum sulfate, aluminum chloride, aluminum nitrate, aluminum hydroxide and pseudo-boehmite.
8. The method according to claim 1, wherein: The weight ratio of the Beta molecular sieve precursor, the small-grain NaY molecular sieve, the dual-microporous material synthesis template, the dual-microporous material synthesis alkali source and the water is 1: (0.1-10): (0-0.4): (0-1): (0-10).
9. The method according to claim 1, wherein: The template for synthesizing the dual microporous material is one or more selected from tetraethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide; The double microporous material synthetic alkali source is one or more selected from sodium hydroxide, potassium hydroxide, sodium oxide and potassium oxide.
10. The method according to claim 1, wherein: The conditions for synthesizing and crystallizing the dual microporous material include: a temperature of 110 to 155° C. and a time of 12 to 60 hours.
11. A Y / Beta composite double microporous material prepared by the method according to any one of claims 1 to 10.
Citation Information
Patent Citations
Preparation of composite double microporous material
CN101376505A
Hydrocracking catalysts containing stabilized aggregates of small crystallites of zeolite y and associated hydrocarbon conversion processes
WO2012122208A1